Simulation Analysis of the Influence of Tooth Surface Pit Morphology on the Dynamics Performance of Face Gear Mesh - He Guoqi; Deng Shujie; He Ying; Yan Hongzhi; Sun Neng; Wang Qilei (Jixie chuandong)
The three dimensional solid model of the face gear with different pit morphology and the simulation model of the face gear transmission system of the pit morphology are established,through the contact collision algorithm of multi- body dynamics,the change regularity of meshing force and output speed of the different pit morphology face gear transmission under certain condition is analyzed.The results show that the influence of the circular pit morphology on the transmission system meshing force is the smallest,the value of transmission error is the lowest,so the transmission stability is optimal.And the experimental conclusion is consistent with the simulation results,the correctness of the simulation is verified.A reasonable basis of oil- lack lubrication model of face gear with pit morphology in the future is provided by the results.